Fear of Falling among Community-dwelling Sedentary and Active Older People - Araya, Alejandra-Ximena; Iriarte, Evelyn (Investigación y Educación en Enfermería, 2021)
Objective. The study sought to compare community-dwelling older people with respect to their level of physical activity and to the fear of falls between a group of sedentary elderly and a group of active elderly. Methods. Cross-sectional descriptive study carried out with 113 community-dwelling older people (45 sedentary and 48 active), users of an outpatient care center of the private health system with a geriatric program in Santiago, Chile. The study measured socio-demographic variables, state of health, comprehensive geriatric assessment, exercise, depression with the Yesavage scale, and fear of falling with the Short Falls Efficacy Scale - International (Short FES-I). Results. Sedentary older people have significantly higher scores in the Yesavage depression scale compared with active older people (4.2 versus 0.8). No statistically significant differences were found when comparing both groups of sedentary and active participants in terms of socio-demographic variables along with health, and functional and cognitive capacity. Regarding the fear of falling, the sedentary had a slightly higher score than the active (12 versus 11), although not significant. Conclusion. This study showed that fear of falling was equal in sedentary and active older people who live in the community, although it was found that sedentary individuals had a higher risk of having a positive screening for geriatric depression in those participants who do not perform physical activity.